2016
DOI: 10.5539/ijef.v8n12p143
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Foreign Portfolio Investment and Its Effects on China

Abstract: Foreign portfolio investment consists of securities and other capital inflows of assets possibly held by other foreign countries. Foreign Portfolio Investment (FPI) provides the investor with indirect ownership of financial assets. This study intends to investigate the economic factors which attract the investors to invest in the host country. We observed what the impact of FPI determinants on the Chinese economy. To elaborate our results we used multiple regression models by using E-views. This study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Hence, if home economy produced less goods and services, foreign investors might see such economy as risky. This is in consonance with Haider, Khan and Abdulahi (2016); Atobrah (2015); Ahmad, Draz and Yang (2015), who noted that domestic economic growth influences foreign investors' decision to invest in an economy. Also, Yahya, Shujahat and Muhammad (2015) found that FPV was associated with dismal economic performance of recipient economy.…”
Section: Diagnostic Testssupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, if home economy produced less goods and services, foreign investors might see such economy as risky. This is in consonance with Haider, Khan and Abdulahi (2016); Atobrah (2015); Ahmad, Draz and Yang (2015), who noted that domestic economic growth influences foreign investors' decision to invest in an economy. Also, Yahya, Shujahat and Muhammad (2015) found that FPV was associated with dismal economic performance of recipient economy.…”
Section: Diagnostic Testssupporting
confidence: 80%
“…This is in line with the findings of Ibrahim and Akinbobola (2017), Okpoto (2015), and Baghebo and Apere (2014. The association between inflation rate and foreign portfolio investment in China had been observed by Haider, Khan and Abdulahi (2016). Negative and insignificant relationship between foreign portfolio investment and the stock market development had been observed by Abel, Ebele and Ndi (2009).…”
mentioning
confidence: 89%
“…UNCTAD (1999) states that FPI involves a transfer of financial assets by way of investment by resident individuals, enterprises, and institutions of one country in securities of another country, either directly in the assets of the companies or indirectly through financial markets. Furthermore, Haider et al (2016) explain that FPI is the capital inflow into the country through foreign investment. It is in the form of stocks and shares securities or debt securities in the host country.…”
Section: Profile Of Foreign Investments In Africamentioning
confidence: 99%
“…The foreign investors speculate on the boom in the market and invest by keeping sight of the economic variables. Haider et al (2016) point out that the trends related to FPI worldwide, especially in the developing economies, have changed in the last century. Daly and Vo (2013) state that the trend of foreign investors investing in a foreign country in the last decade is encouraging.…”
Section: Profile Of Foreign Investments In Africamentioning
confidence: 99%
See 1 more Smart Citation